Métodos de investigación científica - Vásquez Ramírez, Abbon Alex (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2023)
This scientific research methods book aims to provide a detailed and practical guide on the different types of research, the scientific method and the techniques and tools necessary to carry out rigorous scientific investigations, guidelines are provided to assess the quality of research. and best practices are discussed to ensure that the results are valid and reliable. The book has been designed to be used by anyone interested in conducting scientific investigations, from university students to professional researchers.